Fecal shedding of extended-spectrum beta-lactamase-producing Enterobacterales in cats admitted to an animal shelter. Issue 12 (December 2022) - Weese, J Scott; O'Brien, Tyler; Bateman, Shane
Objectives: The objective of this study was to evaluate shedding of extended-spectrum beta-lactamase (ESBL)-producing bacteria in cats admitted to an animal shelter. Methods: Fecal samples were collected from cats admitted to an animal shelter between 12 June and 23 August 2018. Selective enrichment culture for ESBL-producing bacteria was performed and isolates were speciated and tested for selected ESBL genes using PCR. Results: ESBL-producing Enterobacterales were identified in fecal samples from 2/87 (2.3%; 95% confidence interval 0.6–8.0) cats. One isolate was an Escherichia coli that possessed blaCTX-M-1, blaCMY-2 and blaTEM genes. The other was Enterobacter cloacae possessing blaCTX-M-1 and blaCMY-2 . Conclusions and relevance: While the study sample size and prevalence rate for ESBL-producing bacteria were low, these data document that cats admitted to similar shelters could harbor these agents. The risk posed by ESBL-producing bacterium shedding in cats, both to cats and other species, is currently unclear. However, these findings support the need for more investigation of interspecies transmission of ESBL-producing bacteria and ESBL genes, as well as the importance of antimicrobial stewardship and routine infection control measures.